Ten (+1) lessons from conducting a mass casualty in situ simulation exercise in a Canadian academic hospital setting - Tochkin, MA, CEM, Jeffrey T.; Tan, MSc, Hung; Nolan, Caroline; Carmichael, MD, Harrison; Willmore, MD, Andrew; Mastoras, MD, George (Journal of Emergency Management, 2021)
Providing care in a twenty-first century urban emergency department (ED) and trauma center is a complex high-pressure practice environment. The pressure is intensified during patient surge scenarios commonly seen during mass casualty incidents, such that response must be practiced regularly. Beyond clinical mastery of individual patient trauma care, a coordinated system-level response is essential to optimize patient care during these relatively infrequent events. This paper highlights the need to perform exercises in hospitals while providing practical advice on how to utilize in situ simulation for mass casualty testing. Eleven lessons are presented to assist other emergency management professionals, hospital administrators, or clinical staff to achieve success with in situ simulation. Based upon our experience designing and executing an in situ mass casualty simulation within an ED, we offer lessons applicable to any type of disaster exercise. Simulation offers a powerful tool for the conduct of disaster preparedness exercises for staff across multiple hospital departments and professions.